(untitled) (Innovaciones Educativas, 2024)
One of the fundamental pillars of the University of Costa Rica (UCR) is social action, which includes continuing education. In this sense, the School of Topographic Engineering has created the project ED3550 Training and Updating Activities in Topographic Engineering. This project is an opportunity to provide training and updating in relevant and innovative topics to those interested, and to create a link with society to strengthen professional skills and abilities. The training activities are promoted through digital marketing on social networks, e-mail and mobile devices. This has given a national and international projection to the courses and lectures organized, resulting in a wide participation of professionals not only from topographic engineering, but also from other professions such as civil engineering, geography, biology, law and environmental engineering, among others. A systematization of the experience is presented, based on the five-point method proposed by Jara (2018), in which a quantitative analysis of the achievements during the period from 2020 to 2022 is carried out. In summary, the success achieved in two years of project implementation is attributed to the use of digital media for the dissemination of program activities, which has provided an important exposure to different populations and has allowed the EIT to establish a social link and promote professional updating. It is therefore concluded that digital marketing contributes significantly to the knowledge of the target population, which makes it possible to provide adequate solutions to their training needs.